1997
DOI: 10.1002/ana.410420210
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal N‐acetylaspartate in neocortical epilepsy and mesial temporal lobe epilepsy

Abstract: Previous magnetic resonance spectroscopy (MRS) studies have shown that N-acetylaspartate (NAA) is reduced not only in the ipsilateral but also in the contralateral hippocampus of many patients with mesial temporal lobe epilepsy (mTLE). The reason for the contralateral damage is not clear. To test whether the hippocampus is also damaged if the focus is outside the hippocampus, we have measured patients with neocortical epilepsy (NE). Therefore, the goals of this study were to determine if hippocampal NAA is red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
56
7
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 9 publications
4
56
7
4
Order By: Relevance
“…Alternatively, several groups have reported decreased NAA levels estimated by proton magnetic resonance spectroscopy in epileptic patients correlating with increased seizure frequency (Vainio et al, 1994;Vermathen et al, 1997;Mendes-Ribeiro et al, 1998), which appears inconsistent with our results. However, this apparent discrepancy might be explained by the different location of NAA between human epileptic patients and NAA-injected rats.…”
Section: Discussioncontrasting
confidence: 99%
“…Alternatively, several groups have reported decreased NAA levels estimated by proton magnetic resonance spectroscopy in epileptic patients correlating with increased seizure frequency (Vainio et al, 1994;Vermathen et al, 1997;Mendes-Ribeiro et al, 1998), which appears inconsistent with our results. However, this apparent discrepancy might be explained by the different location of NAA between human epileptic patients and NAA-injected rats.…”
Section: Discussioncontrasting
confidence: 99%
“…6 However, it is possible that functional connections exist between the hippocampi and may contribute to seizure propagation, whereas seizures arising from the neocortex do not affect hippocampal metabolism. …”
Section: Discussionmentioning
confidence: 99%
“…However, in neocortical epilepsy (NE), no MRS imaging (MRSI) changes in the hippocampus were found, suggesting that repeated seizures in NE do not lead to hippocampal impairment. 6 Reductions of NAA are reversible in some diseases. 4,5,7 If the NAA reduction in the contralateral hippocampus is due to secondary alterations caused by repeated seizures, these changes might be reversible with reduction of seizure frequency.…”
mentioning
confidence: 99%
“…1 1 H MRS imaging (MRSI) measures a number of metabolites, including N-acetyl aspartate (NAA), a marker of neuron viability and density. 2 1 H MRSI has shown NAA is reduced in the epileptogenic hippocampus, [3][4][5] frequently even when the MRI is normal, 3 suggesting NAA can help identify the seizure focus. Previous studies suggested 1 H MRSI may predict surgical outcome, but most of these subjects had MTS on MRI.…”
mentioning
confidence: 99%
“…Spectra from 10 patients and 16 control subjects were processed using Siemens LUISE software (Iselin, NJ), 5 whereas spectra from five patients and 12 control subjects were processed using the FITT program. 6 In order to combine these results, standardized z scores were generated for each patient by comparing their NAA ratios with their contemporaneous normal control subjects.…”
mentioning
confidence: 99%